A new species of Philodendron (Araceae) and a key to Brazilian Atlantic Forest species of P. subgenus Pteromischum - Calazans, Luana S.b.; Sakuragui, Cassia M. (Phytotaxa, 2013)
This paper describes and illustrates a new Philodendron subgenus Pteromischum species from Espírito Santo State, in Southeastern Brazil, including information on its conservation in a high priority area for conservation of the Atlantic Forest. The work also includes a key to the Brazilian Atlantic Forest species of the subgenus.